1999
DOI: 10.1159/000029361
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Thymoma with Long-Term Survival by Extensive Reoperation

Abstract: The recurrence of invasive thymoma is often observed; however, no accepted treatment of recurrent invasive thymoma has yet been established. We herein report a 41-year-old woman with invasive thymoma and pleural dissemination who demonstrated long-term survival after undergoing 4 operations. Based on our findings, reoperation is thus suggested in patients with intrathoracic recurrence and long-term survival can be expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…6,19,20 Surgery is commonly recommended for managing recurrence, and some have reported the benefit of complete surgical extirpation of the recurrent disease. 20,21 As presented in Table 3, however, once the disease recurs, it is difficult to control it, indicating that salvage treatment for the recurrence of stage II or III thymoma may not be effective. In terms of OS in recurrent thymoma, Ruffini et al 6 reported the 5-and 10-year survival rates to be 46.9% and 35.2%, respectively, and Regnard et al 20 51% and 43%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…6,19,20 Surgery is commonly recommended for managing recurrence, and some have reported the benefit of complete surgical extirpation of the recurrent disease. 20,21 As presented in Table 3, however, once the disease recurs, it is difficult to control it, indicating that salvage treatment for the recurrence of stage II or III thymoma may not be effective. In terms of OS in recurrent thymoma, Ruffini et al 6 reported the 5-and 10-year survival rates to be 46.9% and 35.2%, respectively, and Regnard et al 20 51% and 43%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…When a new pleural relapse is found, an iterative resection should be considered. 24 We have performed 3 iterative resections of pleural implants and in 1 case a third operation was performed; all the patients were long-term survivors and 2 of them are still alive and well. We can conclude that reoperation for thymoma pleural recurrences is feasible and safe.…”
Section: Discussionmentioning
confidence: 99%
“…The main treatment method is complete surgical resection that improves the long-term survival rate 12 . In previous large-scaled studies, complete resection is an independent prognostic factor by multivariate analysis, and the mortality rate is reported to be 2.5% 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Our patient received radiation therapy with a dose of 5,040 cGy after pleural node excision through video-assisted thoracoscopy. Only a few cases of tumor recurrence after surgical resection of thymoma have been reported 1,[12][13][14] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation